Mismatch Negativity Latency as a Biomarker of Amnestic Mild Cognitive Impairment in Chinese Rural Elders - Ji, Li-Li; Zhang, Yuan-Yuan; Zhang, Lane; He, Bing; Lu, Guo-Hua (Frontiers in Aging Neuroscience, 2015)
The aim was to evaluate the Mismatch Negativity (MMN) component, a correlate of the automatic detection of changes in the acoustic environment, in healthy adults and adults with aMCI. 43 mild amnestic cognitive impairment (aMCI) subjects and 43 healthy Chinese older adults were arranged into experimental group and control group respectively. Their MMN amplitude and latency were measured at the FZ, FCZ and CZ electrode sites under a passive auditory oddball task. The results showed that the latencies obtained from the FZ, FCZ and CZ electrode sites were significantly longer in the aMCI adults than in the control adults (P<0.01) while there were no significant differences in MMN amplitude between two groups(P＞0.05). The MMN latency was found to be a sensitive and specific biomarker of aMCI.